Critical dysregulated signaling pathways in drug resistance: highlighting the repositioning of mebendazole for cancer therapy - Aliabadi, Amin; Moradi, Seyed Zachariah; Abdian, Sadaf; Fakhri, Sajad; Echeverría, Javier (Frontiers in Pharmacology, 2025)
BackgroundCancer drug resistance significantly reduces the effectiveness of current anticancer treatments. Multiple dysregulated signaling pathways drive cancer initiation, progression, and related drug resistance. This highlights the need for developing new multi-targeting drugs that are more cost-effective, have fewer side effects, and remain effective against cancer. Drug repurposing offers a promising solution to expensive targeted therapies and helps overcome drug resistance. Mebendazole (MBZ), albendazole, flubendazole, and oxfendazole are broad-spectrum anti-helminthic drugs from the benzimidazole family.PurposeTherefore, MBZ demonstrated potential in suppressing the growth of various cancer cells, both in vitro and in vivo. Consequently, we thoroughly reviewed MBZ as a therapeutic option against cancer and related drug resistance.Results and discussionIn this study, we identified MBZ as a promising cancer treatment that works through multiple mechanisms such as regulating tumor angiogenesis, autophagy, and apoptosis, modulating key signaling pathways, boosting antitumor immune responses, and inhibiting matrix metalloproteinases activity—all of which are major factors in cancer drug resistance. Additionally, the development of new MBZ delivery systems aims to address its pharmacokinetic limitations. While the anticancer effects of MBZ are encouraging, further research is needed before it can be used clinically.ConclusionExtensive data from in vitro, in vivo, and clinical trials support MBZ’s anticancer potential and highlight the need for innovative delivery methods, including polymeric nanoparticles, nanostructured lipid formulations, micelles, nanosuspensions, and beyond.